High-sensitive cardiac troponin I (hs-cTnI) concentrations in newborns diagnosed with spinal muscular atrophy - Johannsen, Jessika; Weiss, Deike; Driemeyer, Joenna; Olfe, Jakob; Stute, Fridrike; Müller, Ferdinand; Schütt, Marion; Trollmann, Regina; Kölbel, Heike; Schara-Schmidt, Ulrike; Kirschner, Janbernd; Pechmann, Astrid; et al. (Frontiers in Pediatrics, 2023)
Background Spinal muscular atrophy (SMA) is a genetic neurodegenerative disease leading to muscular weakness and premature death. Three therapeutic options are currently available including gene replacement therapy (GRT), which is potentially cardiotoxic. High-sensitive cardiac troponin I (hs-cTnI) is widely used to monitor potential cardiac contraindications or side effects of GRT, but reference data in healthy newborns are limited and lacking in neonates with SMA. The aim of this study is to determine the range of pre-therapeutic hs-cTnI concentrations in neonates with SMA and to provide guidance for the assessment of these values. Methods Hs-cTnI levels, genetic and clinical data of 30 newborns (age range 2–26 days) with SMA were retrospectively collected from 6 German neuromuscular centers. In addition, hs-cTnI levels were measured in 16 neonates without SMA. Results The median hs-cTnI concentration in neonates with SMA was 39.5 ng/L (range: 4–1205). In 16 newborns with SMA, hs-cTnI levels were above the test-specific upper reference limit (URL). Exploratory statistical analysis revealed no relevant correlation between hs-cTnI levels and gender, gestational age, mode of delivery, SMN2 copy number, symptoms of SMA or abnormal cardiac findings. Discussion Our results suggest higher hs-cTnI plasma levels in newborns with and without SMA compared to assay-specific reference values generated in adults. Given the wide range of hs-cTnI values in neonates with SMA, hs-cTnI levels must be determined before treatment in each patient and post-treatment elevations should be interpreted in the context of the course rather than as individual values.